GASTRODIPLOMACY: HARNESSING CULINARY TRADITIONS TO BOOST BOROBUDUR'S NATIONAL TOURISM STRATEGIC AREA POLICY - Widyantoro, Sigid; Akhni, Ghaziah Nurika; Noormansyah, Reza; Rahmawati, Yuni; Hidayat, Yudistira Wahyu (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
Borobudur, a UNESCO World Heritage site in Central Java, Indonesia, plays a crucial role in the nation's tourism by enhancing economic growth and cultural prestige. The Indonesian government has designated Borobudur as part of the National Tourism Strategic Areas (KSPN) to boost tourism while preserving cultural heritage. A key strategy in this initiative is gastrodiplomacy, which uses Indonesia's diverse culinary traditions to attract international tourists, particularly the growing